Adaptation of Iron Craftsmen during the Pandemic in Bintau Village, West Passi District, Kab. BolaangMongondow - Mokodongan, Safrial; Salem, Veronike E.T; Santie, Yoseph D.A (Laboratorium Program Studi Pendidikan Sosiologi Unima, 2025)
The problem in this research is to look at the adaptation of iron craftsmen in Bintau village during the pandemic with a problem focus, namely how iron craftsmen can adapt during the pandemic in meeting the economic needs of their families using qualitative research methods with interview and observation data collection techniques. What was found were several adaptation efforts made by dangdut music workers, namely, first, by continuing to sell during the pandemic using minimal communication media and not selling widely on social media because permission was constrained and if they posted they would be banned or blocked because they were considered dangerous posts, and secondly, in order to meet their family's needs, they have to work side jobs processing their agricultural products.